An Exploratory Needs Analysis of Parents Diagnosed with Cancer. Issue 3 (3rd July 2019) - Schiena, Elena; Hocking, Alison; Joubert, Lynette; Wiseman, Fiona; Blaschke, Sarah
ABSTRACT: The purpose of this study was to explore the experiences of parents and co-parents where one parent was diagnosed with cancer with specific interest in the impact of the disease on their role as a parent and the supports that were found to be useful in managing the ongoing care of their children. A qualitative research method using semi-structured interviews and thematic network analysis techniques was used. Participants included adult English-speaking parents receiving treatment for a new diagnosis of cancer at a major tertiary oncology research and treatment centre, with prior social work involvement. Participants reported multiple, complex layers of need. Four salient themes were evident: (a) emotional impact of a cancer diagnosis on the patient, (b) accessing professional supports, (c) children's understanding, and (d) meeting children's needs. Parents described difficulties in managing emotionally, physically, and existentially. Accessing supports within the healthcare service and community was paramount, as was guidance around communicating with children. Receiving a proactive service from a social worker was highly regarded. The results demonstrate that it is essential to respond to the needs of parents with cancer in order to minimise prolonged emotional distress. IMPLICATIONS: Parents diagnosed with cancer have unique needs including concern about the impact on their children and families. Social workers should be proactive in identifying patient needs and ensuring services and supports are provided in a timely way.